2014
DOI: 10.1016/j.nuclphysb.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-quartic interaction for a scalar field in an extended DFR noncommutative space–time

Abstract: The framework Doplicher-Fredenhagen-Roberts (DFR) of a noncommutative (NC) space-time is considered as a alternative approach to study the NC space-time of the early Universe. In this formalism, the parameter of noncommutative θ µν is promoted to a coordinate of the space-time, and consequently, we are describing a field theory in a space-time with extra-dimension. Consequently, there is a canonical momentum associated to this new coordinate in which the effects of a new physics can emerge in the propagation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…An an extended Hilbert space with ten dimensions (four Minkowskian and six θ coordinates) was constructed. Recently, it was demonstrated [15] precisely that the formalism has a conjugate momentum for the θ coordinate and several elements of a DFR QFT were constructed [22][23][24]. However, to avoid unitarity we will keep the time components of θ µν equal to zero, namely, θ 0i = 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An an extended Hilbert space with ten dimensions (four Minkowskian and six θ coordinates) was constructed. Recently, it was demonstrated [15] precisely that the formalism has a conjugate momentum for the θ coordinate and several elements of a DFR QFT were constructed [22][23][24]. However, to avoid unitarity we will keep the time components of θ µν equal to zero, namely, θ 0i = 0.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, we have been concentrated in the construction of a NC QFT concerning the DFR formalism [22][23][24][25]. In this work we, following this DFR QFT quest, have constructed the DFR basis for a standard model after the construction of a DFR metric tensor.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, it does not require any quantum gravity scenario. The approach here is very different from the ones investigated in [18][19][20]. Here, we will show a direct approach to construct the scalar field.…”
Section: Quantum Nc Scalar Field Theorymentioning
confidence: 94%
“…In papers published by two of us [18][19][20], one can see that the construction of the commutation relations between the bosonic/fermionic fields with themselves and with its associated momenta are missing. It is our intention in this section to fill this gap.…”
Section: The Dfr Scalar Fieldmentioning
confidence: 99%
“…Here a general solution for the DFRA complex scalar fields has also been constructed using the Green's function technique. It has been shown that, in DFRA scalar model with φ 4 interaction at the one-loop level, the UV/IR mixing does not exist [19]. The covariant Dirac equation has been derived in DFR space-time from the generalised DFRA Klein-Gordon equation [20].…”
Section: Introductionmentioning
confidence: 99%